Peran Manajemen SDM dalam Mendukung Kinerja UMKM: Studi pada Keripik Balado 4x7 Kota Padang - Aprilinda Putri Rieyani; Nia Ramdhani Fitri; Jihan Dwi Salzabilla; Muhammad Zacky Yuvan Ramadhan; Muhammad Febrian; Chintya Ones Charli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in promoting regional economic growth and creating employment opportunities. One of the key factors influencing MSME performance is effective human resource management (HRM). This study aims to analyze the role of human resource management in supporting the performance of Keripik Balado 4x7 MSME in Padang City. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the business owner and employees. The findings indicate that the implementation of HRM functions, including recruitment, employee training, job allocation, motivation, and performance evaluation, has contributed positively to productivity, product quality, and customer service. However, several challenges remain, such as the limited number of employees and the lack of structured employee competency development programs. Therefore, improving human resource management practices is essential to enhance competitiveness and ensure the long-term sustainability of the business.